Numerical simulation of non‐Newtonian polymer film flow on a rotating spoked annulus. Issue 25 (3rd March 2017) - Miah, Md Salim; Hossain, Mohammad Sayeed; Ashraf, Muhammad Arif; Al‐Assaf, Saphwan; McMillan, Alison
ABSTRACT: The current study presents results from a series of numerical analyses of non‐Newtonian liquid film formation on a rotating spoked annulus. The film flow of a common type of polyester, poly(ethylene terephthalate) (PET), on a vertically rotating disk was modeled numerically. Two different molecular weights, corresponding to different viscosities for PET, and under flow at different rotating speeds, were considered. The film thickness profile was obtained at different radial and angular positions of the rotating disk in the simulations, which is beneficial in calculating the volume of polymer taken up by the rotating disk and also in calculating the volumetric flow rates on the disk. Two types of disks, including a standard solid disk and a number of hollow disk designs with spoked annuli, were considered, and the film flow was modeled using a volume of fluid computational fluid dynamics analysis. The analyses of flow over spoked annulus designs highlighted the advantage of such designs over the use of a conventional solid disk. It was found that the variation in the film thickness for the spoked annulus was lower than that for the conventional solid disk. The parametric study also provided a favorable spoked annulus design for which the film thickness was essentially constant. A constant film thickness would provide a constant film flow, which can be a benefit to many industrial applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44943. Abstract :